Efficacy of Anti-seizure Medications, Quinidine, and Ketogenic Diet Therapy for KCNT1-Related Epilepsy and Genotype-Efficacy Correlation Analysis - Lin, Zehong; Sang, Tian; Yang, Ying; Wu, Yuan; Dong, Yan; Ji, Taoyun; Zhang, Yuehua; Wu, Ye; Gao, Kai; Jiang, Yuwu (Frontiers in Neurology, 2022)
AIM: To evaluate the treatment efficacy of anti-seizure medications (ASMs), quinidine, and ketogenic diet therapy (KDT) for KCNT1-related epilepsy and to explore genotype-efficacy correlations. METHOD: We collected the treatment data for KCNT1-related epilepsy cases from our hospital’s medical records and the literature. In total, 50 patients received quinidine, 23 received KDT, and 15 received ASMs; all ASM data were from our hospital owing to the lack of detailed ASM data in the literature. The efficacy rates (ERs) of the treatments were compared; an ER that reduced the number of seizures by ≥50% was considered positive. Treatment efficacy according to genotype was also assessed. RESULTS: The ERs for the 30 patients at our hospital were 40%, 26.7%, 30%, and 44.4% for all treatments, ASMs, quinidine, and KDT, respectively. For all patients (ours and those in previous reports), the overall ERs for quinidine and KDT were 26.0% and 43.5%, respectively (P = 0.135). The ERs for quinidine and KDT in functional domain variant-related epilepsy differed significantly (20.6% vs 53.8%; P = 0.037). INTERPRETATION: KDT may be better at treating KCNT1-related epilepsy than quinidine; ASMs were the least effective. KDT is a viable treatment option for functional domain variant-related epilepsy.